PERAN PEMERINTAH DAERAH DALAM PENGAWASAN DAN PENGENDALIAN PEREDERAN ALKOHOL BERDASARKAN PERATURAN DAERAH KOTA BEKASI NOMOR 17 TAHUN 2009: The Role Of Local Government In Supervising And Controlling The Distribution Of Alcoholic Based On Bekasi City Regional Regulation Number 17 Of 2009 - Michael Rudolf; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2025)
One of the concerning issues that should receive in-depth attention from the government is the illegal alcoholic beverages that have harmful effects on health. In Indonesia, there are several illegal alcohol factories where alcohol is not taxed, sold outside official channels, and lacks government supervision. The problem addressed in this research discusses the obstacles faced by the Bekasi City Government in supervising and controlling the circulation of alcoholic beverages in Bekasi City based on Bekasi City Regional Regulation Number 17 of 2009, as well as the efforts made by the Bekasi City Government in supervising and controlling the circulation of alcoholic beverages based on Bekasi City Regional Regulation Number 17 of 2009. This study uses a normative legal approach by utilizing secondary data, supported by primary data. The research is descriptive, and conclusions are drawn using a deductive method. The results and conclusions of this research indicate that the Bekasi City Government is committed to creating a good environment for its citizens. Therefore, the Satpol PP (Public Order Agency) plays an important role in patrolling and monitoring the circulation of alcoholic beverages despite facing challenges and obstacles, such as backing from nightclub owners.